2014
DOI: 10.1007/s13277-014-2696-0
|View full text |Cite
|
Sign up to set email alerts
|

WWP1 as a potential tumor oncogene regulates PTEN-Akt signaling pathway in human gastric carcinoma

Abstract: Whelming evidence has demonstrated that WW domain containing E3 ubiquitin protein ligase 1 (WWP1) participates in a wide variety of biological processes and is tightly related to the initiation and progression of many tumors. Currently, although mounting evidence supports a role of WWP1 in tumor promotion and tumorigenesis, the potential roles of WWP1 and its biological functions in gastric carcinoma are not fully understood. Here, we found that WWP1 messenger RNA (mRNA) and protein were highly expressed in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Notably, high WWP1 expression predicted a higher metastatic potential and poor prognosis in patients with CSCC, which differed from the results of a previous study in breast cancer patients, 16 but was consistent with a study in patients with gastric carcinoma. 13 These findings imply that WWP1 may represent a new biomarker for metastasis and prognosis in patients with CSCC.…”
Section: Discussionmentioning
confidence: 90%
“…Notably, high WWP1 expression predicted a higher metastatic potential and poor prognosis in patients with CSCC, which differed from the results of a previous study in breast cancer patients, 16 but was consistent with a study in patients with gastric carcinoma. 13 These findings imply that WWP1 may represent a new biomarker for metastasis and prognosis in patients with CSCC.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, WWP1 is also frequently amplified in oral cancer [113]. Furthermore, increased WWP1 mRNA and protein levels have been reported in hepatocarcinoma cell lines and tissues [114], as well as in gastric tumors [115]. Collectively, these findings strongly suggest a role for WWP1 in oncogenesis.…”
Section: Wwpsmentioning
confidence: 86%
“…WWP1 delays cellular senescence and negatively regulates the TGFβ signaling pathway, which regulates cell proliferation, differentiation, apoptosis, and migration in numerous cell types [16, 17]. Furthermore, it has been reported that WWP1 acts as an oncogenic factor in GC [18]. In the present study, we used bioinformatic prediction and experimental confirmation studies to demonstrate that WWP1 plays a pivotal role in human GC and is a putative direct target of miR-584-5p.…”
Section: Introductionmentioning
confidence: 85%